Black Lycium barbarum polysaccharide attenuates LPS-induced intestine damage via regulation gut microbiota - Yan, An; Ding, Houkang; Liu, Junjun; Bi, Chongliang; Han, Zhaoqing; Wang, Zhennan; Nawaz, Shah; Shen, Yizhao; Liu, Shudong (Frontiers in Microbiology, 2023)
Lycium barbarums are homology of medicine and food plants for ages in China, which enhances the metabolism, anti-oxidant activity, and immunomodulation. However, little information is available about the effect of black lycium barbarum polysaccharide (BLBP) on lipopolysaccharide (LPS) induced intestine damage in mice. Hence, the current study was performed to explore the attenuation effect and microbiota regulation of BLBP on LPS damaged induced mice. A total of 70 mice were randomly divided into five groups named as negative control (GA), LPS (GB), and treatment groups (GC, GD, GE). Mice in group GC (100 mg/kg), GD (200 mg/kg), and GE (400 mg/kg) were treated by BLBP via gavage for 19 days, while mice in groups GC and GL were treated with an equal volume of normal saline. On day 19, mice in groups GB, GC, GD and GE were treated with 10 mg/kg LPS, and after 24 hours all mice were euthanized to collect intestine samples for pathological examination and microbiota sequencing. Results showed a non-significant difference in body weight gain among groups(mention groups name), however,groups GC and GE showed decreased weight gain. H&E examination revealed that the integrity of intestinal villi was destroyed by LPS, while BLBP supplement alleviated intestinal damage with increased villus heights and decreased crypt depth. A total of over 59 000, 40 000, 50 000, 45 000 and 55 000 raw sequences were found in groups GA, GB, GC, GD, and GE, respectively. LPS challenge decreased alpha diversity indexes significantly (p<0.05), while nonsignificant difference was found between different BLBP treatment groups and group GA. A total of 8 phyla and 13 genera were found among five mouse groups, and BLBP partly restored the bacterial abundance in mice. LPS changed 282 metabolic pathways in KEGG L2, 77 metabolic pathways in KEGG L3, and 205 metabolic pathways in MetaCyc. BLBP supplemented groups especially GE showed reverse effects on those metabolic pathways . The current study revealed that BLBP can effectively decrease intestinal damage through regulation of intestinal microbiota, which may provide new insights to prevention of intestinal disease by using food and medicine homologous of lycium ruthenicum.